Eco-friendly synthesis of fused pyrano[2, 3-b]pyrans via ammonium acetate-mediated formal oxa-[3 + 3]cycloaddition of 4H-chromene-3-carbaldehydes and cyclic 1, 3-dicarbonyl compounds. Issue 57 (16th September 2020) - Osyanin, Vitaly A.; Osipov, Dmitry V.; Semenova, Irina A.; Korzhenko, Kirill S.; Lukashenko, A. V.; Demidov, Oleg P.; Klimochkin, Yuri N.
Abstract : We report the eco-friendly synthesis of fused pyrano[2, 3- b ]pyrans via ammonium acetate-mediated formal oxa-[3 + 3]-cycloaddition of 4 H -chromene-3-carbaldehydes and cyclic 1, 3-dicarbonyl compounds. Abstract : Various substituted polycyclic pyrano[2, 3- b ]pyrans were synthesized via the condensation of 4 H -chromene-3-carbaldehydes and their areno-condensed analogues with hetero- and carbocyclic 1, 3-dicarbonyl compounds in acetic acid. Ammonium acetate was used as a green catalyst for the reaction. The process also involves the subsequent Knoevenagel condensation and 6π-electrocyclization of the 1-oxatriene intermediates formed. Fused pyridines were isolated as the products of the conjugated addition of ammonia to 1-oxatriene intermediates while using carbocyclic 1, 3-dicarbonyl compounds and increasing the reaction time, indicating the reversibility of the electrocyclization stage. The calculated values of the Gibbs free energies and reaction rate constants for the 1-oxatriene – 2 H -pyran equilibrium also testified to the irreversibility of pyrano[2, 3- b ]pyran formation in the case of using of heterocyclic 1, 3-dicarbonyl compounds.